Double Alkynylation of Quinoline-5,8-diones and their In-silico and Antimicrobial Studies - MA Ezeokonkwo; JA Ezugwu; SN Okafor; EA Onoabedje; EU Godwin-Nwakwasi; FN Ibeanu (Journal of Applied Sciences and Environmental Management, 2018)
A double alkynylation of quinoline-5,8-dione to furnished bis-alkynylquinoline-5,8-dione in good yields and their in silico and antimicrobial studies is described. This was achieved by cross-coupling of 6,7- dibromoquinoline-5,8-dione with various terminal alkynes in the presence of bis(triphenylphosphine) palladium(II) chloride as a pre-catalyst and tetrabutyl ammonium fluoride trihydrate. The structures of the synthesised compounds were confirmed by UV/Visible, Fourier Transform-Infrared and 1H and 13C-NMR spectral data. The synthesised compounds exhibited good activity against Escherichia Coli 1, Escherichia Coli 12, Klebsiella Pneumonia, Pseudomonas aeroginosa and Staphylococcus aureus compare to the gentamycin and ampicillin. Molecular docking simulation study of the binding interactions of compounds with receptors disclosed significant binding affinity for P. aeruginosa LpxC than the E. coli glutaredoxin.